Did living standards actually improve under state socialism? Real wages in Bulgaria, 1924-1989 - Matthias Morys; Martin Ivanov Ivanov (European Historical Economics Society (EHES), 2024)
We challenge the view that Centrally Planned Economies functioned well until the early 1970s, delivering high economic growth and better living standards. Judged by real wages as the most widely used historical living standard indicator, only in the 1970s did Bulgarian living standards surpass levels achieved already four decades earlier. Our findings are particularly discomforting for the rural population which was the big loser of collectivization and forced industrialization policies after 1947. Wages increased throughout the 1970s and the 1980s, but far less so than Maddison's GDP per capita estimates which are often used as a proxy for living standards.
Keywords: E01; N14; N54; N64; P2; P51; 330; real wages; state socialism; structural transformation